Variation of morphological response of cayenne pepper cultivars to phenoxaprop-p-ethyl herbicide - Taqiya, Nurul Rifqi; Purwanto, Edi; Suratman, Suratman (JPBIO (Jurnal Pendidikan Biologi), 2025)
In the cultivation of cayenne pepper (Capsicum frutescens L.), there is a problem with weeds. The use of herbicides for weed control can also trigger phytotoxic reactions in cultivated plants. The purpose of this study was to determine the morphological response of various cultivars of cayenne pepper to exposure to the Phenoxaprop-p-ethyl herbicide. This study employed a completely randomized design. The research data were analyzed using ANOVA and Kruskal-Wallis statistical tests. The study's results revealed a strong biphasic (hormesis) response pattern, where a dose of 55 g/L triggers growth, while a dose of 110 g/L causes phytotoxicity.   .